Application of airborne radiometric method in geologic mapping of Malufashi area and Environs, Northwestern Nigeria - Stephen Onyejiuwaka, Ibe; Charity Nkiru, Nwokeabia (International Journal of Advanced Geosciences, 2020)
In this study, the airborne radiometric data over Masufashi Area of Katsina State and Environs, Northwestern Nigeria were acquired, processed and gridded to generate the concentration maps of percentage Potassium, equivalent Thorium and equivalent Uranium in order to carry out the geologic mapping of the area. Additionally, the abundance ratios, U/Th, U/K and Th/K and the ternary images of the three radioactive elements were produced. The images obtained from the radiometric data showed that the study area comprises five major rock types, based on their variation in the concentration of the three radioactive elements. The actual extent, boundary and distribution of the rock units within the study area were defined; hydrothermal alteration zones were mapped. The altered zones were noted to be associated with mineralization in the quartzite rich schist formation. The interpretation also proved valuable in demarcating some rock types with different properties. The delineated geology and hydrothermally altered zones led to the identification of nine zones with the potentials of gold mineralization. The delineated structures aided the design of the geologic map of the study area. This research showed the value added by airborne geophysics in geologic mapping and recommends the analysis of airborne data as a major phase during reconnaissance survey, prior to geologic mapping.Â Â